The Islamic concept of education according to Shaykh 'Abdu's-Samad of Pelembang and its significance in relation to the issue of personality integration. - Muhammad Uthman El-Muhammady, (Universiti Kebangsaan Malaysia, 1972)
An attempt is made in this paper to discern the salient features of the Islamic educational doctrine and method in the matrix of the sufi tradition as expressed by one of the most outstanding figures in the landscape of Islamic intellectuality in this region, the 18th century Shaykh 'Abdu's-Samad of Palembang (rh). He sees the educational process as the process of purifying the base metal of the fallen soul from all the dross, and transmuting it-by means of the spiritual alchemy available in the Islamic Tradition-into a soul of gold which glitters with the spiritual virtues. From another point of view, it is seen as a journey of the human self towards its Centre-Origin, away from the periphery towards the centre of the personality. Cosmologically, it is-qualitatively-a journey from the Realm of the Sensible right up to the level of cosmic manifestation related nearest to the Absolute, in which the Absolute is realised in spritual experience. This makes religious and spiritual verities no more articles of belief, but matters of direct experience which leaves no room for doubt.